Optimization of the educational process of medical higher education institutions through the information and educational environment - O. A. Murzina; O. M. Raznatovska; O. I. Pototska; N. O. Nahorna (Морфологія, 2020)
Background. Improving the effectiveness of training of future highly qualified personnel requires the improvement of existing and search for new forms and methods for organizing the educational process. Such approach requires the use of complexes of technical and didactic means that ensure the interconnection between classroom and non-classroom forms of the educational process. Objective. To analyze the existing conditions for the implementation of information and educational environment. Methods. Analysis of theoretical sources on the problem of the use of the information and educational environment in higher medical education, studying and generalization of leading experience in teaching student courses using information and communication technologies. The analysis of the results of the efficiency of implementation of the educational and informational environment has been carried out on the departments of phthisiology and pulmonology, histology, cytology and embryology, medical physics, biophysics and higher mathematics and analytical chemistry. Results. The article presents certain results of the work of lecturers concerning the development and use of the informational and educational environment in the context of continuing learning of present-day information-oriented society. Creating information and educational environment that supplies interaction between lecturers and students in classroom through interactive forms of communication on the basis of edХ platform promotes the optimization of the learning process. The basic principles of providing innovative approaches, methods, technologies of the uniform informational and educational environment of higher education medical institutions are substantiated. The necessity of disclosing the experience of higher education institutions regarding the creation of the informational and educational environment as part of the optimization of the student's educational process is emphasized. The experience of using new learning form confirmed the simplicity and interactivity of interaction of the student and the lecturer, gives the wide opportunities for learning process arrangement, enables the student to model learning process individually, as well as new forms of learning process supervision. Conclusion. In our opinion, online courses based on edX platform facilitate the optimization of the learning process in higher education institutions. The prospect of further work is the continuation of the development and implementation of the online course for students on edX platform in the learning process.